The Textiles from Gintarai Cemetery - Pečeliūnaitė-Bazienė, Elvyra (Archaeologia Lituana, 2002)
Very few textiles were found in the cemetery. Even a smaller portion of them survived before they were investigated in the laboratory. The only data about the unsaved portion are those recorded by the initial investigator – I. Jablonskis.The following elements of the textile material were investigated: the fabric, its spinning direction, the weaves, the thread-count. The textiles of the cemetery are all of wool. The acidity of soil is high and flax did not survived. Various types of weave were noted. The four shed 2/2 twill is predominating. Three shed 2/1 twill and four shed diamond twill were also found.The material of the Gintarai cemetery was not distinguishable from any of the other textile material found in cemeteries of West Lithuania and dated to the Roman period. All the threads of textiles have different spinning direction SZ (ZS). It appears that this spinning type was one of the most popular at that time in the whole territory of Lithuania. By the thread count in the textiles, it can be said that the quality of type III and IV predominate. Most of textiles probably were dyed with natural dye, but the dye was not identified. No starting borders or selvages were found.The fibre, the thread count, and the weaves in the textile show that they could have been locally produced. Because of the limited textile material, it is difficult to come to any more detailed conclusions.